Perspectives on Pyrochlores, Defect Fluorites, and Related Compounds: Building Blocks for Chemical Diversity and Functionality - Lumpkin, Gregory R.; Aughterson, Robert D. (Frontiers in Chemistry, 2021)
In this article we provide some perspectives on a range of pyrochlore and defect fluorite type compounds with nominal A2B2O7, A2BO5, ABC2O7, and other stoichiometries. Typically, the phase transformations and stability fields in these systems are mapped as a function of the ionic radii of the A- and B-site cations, e.g., the A/B cation radius ratio (rA/rB). This provides a useful guide to compatible structures and compositions for the development of advanced materials. Pyrochlore commonly transforms to a defect fluorite structure at high temperature in many systems; however, it is not uncommon to observe defect fluorite as the initial metastable phase at low temperature. The patterns of order-disorder observed in these materials are primarily due to the energetics of layer stacking, the defect formation and migration energies of cations and anions, or modulations of the parent cubic structure in 3+n dimensional space. The first lead to predominantly non-cubic derivatives of the parent defect fluorite structure (e.g., zirconolite polytypes), the second control the order-disorder processes, and the latter lead to a variety of subtle additional scattering features within the cubic parent structure. Although the energetics of cation disorder and anion-vacancy disorder have become more accessible via atomistic approaches (e.g., MD and DFT), we continue to find interesting physical-chemical problems in these materials. For example, although there are significant differences in composition (Tb/Zr ratio and O content) between Tb2Zr2O7 and Tb2ZrO5, both of which are defect fluorites, we note that the modulations found in these two compounds by electron scattering are virtually identical with regard to the direction and magnitude of displacement from the normal Bragg diffracted beams. This suggests that neither the A/B cation ratio nor the oxygen stoichiometry have a significant effect on the modulations. The general observations on the systems of compounds noted in this paper rest primarily in the context of industrial materials for nuclear waste disposal, potential applications in inert matrix fuel designs, and other important technological applications such as ionic conductivity, electrical conductivity, and magnetism.